ANALISA TINGKAT KEPUASAN PELANGGAN TERHADAP PENJUALAN BEAUTY PRODUK PADA ONLINE SHOP DENGAN MENGGUNAKAN METODE NAIVE BAYES - Donny Maulana; Emi Lia Nurjanah (Jurnal SIGMA, 2019)
The development of technology is now making it easier and pampering humans, one example that we have known for a long time is shopping online. Besides that customer satisfaction becomes the main target in the business world, because customers are the main foundation in the establishment of a company and become the main goal. Efforts to improve customer satisfaction services in one of the stores in the biggest marketplace in shopee namely DeBeautyHouse, the authors analyze the level of satisfaction in the online shop through existing assessment data, as for the attributes that affect customer satisfaction, namely, product name, product type, product quality , product prices and product shipments. The method used in this study is Naive Bayes to determine the level of data accuracy. The results of this study obtained an accuracy rate of 96.00% with a recall value of 95,24% and a percision value of 100,00%. Keywords : Customer Satisfaction, Online Shop, Naive Bayes